WAKAF DAN PENDIDIKAN: Studi Kasus di Kabupaten Kudus Jawa Tengah (ZISWAF: Jurnal Zakat dan Wakaf, 2015)
Waqf is one of the Islam teachings that aims to draw closer to God. Asidefrom being a religious, waqf have an important role in helping to providepublic facilities. This study aims to determine the contribution of waqf inproviding educational facilities in Kudus. The data that is used came fromthe documentation and analyzed by method Angka Partisipasi Kasar (APK).The results show that waqf in Kudus contribute in providing a means ofeducation both formal and non-formal. A total of 79.0% of formal educationmeans early childhood level, 23.4% of formal education means primary level,62.3% junior secondary level education facilities, and 68.8%, means of formaleducation at the senior secondary level provided by waqf in Kudus. In addition,formal education institutions waqf in Kudus also able provide 15.7% of earlychildhood age level, 27.1% of the population aged primary school level, 45.0%of junior high school age level, and 41.5% of high school age level. As for themeans of non-formal education, the waqf in Kudus used to build a boardingschool, Madrasah Diniyah and Orphanage.